2021
DOI: 10.3389/fnins.2021.707675
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity and Motor Rehabilitation in Multiple Sclerosis: A Systematic Review on MRI Markers of Functional and Structural Changes

Abstract: Background: Motor rehabilitation is routinely used in clinical practice as an effective method to reduce progressive disability gain in multiple sclerosis (MS), but rehabilitation approaches are typically unstandardized, and only few studies have investigated the impact of rehabilitation on brain neuroplasticity.Objective: To summarize and critically analyze studies applying MRI markers of functional connectivity and structural changes to assess the effect of motor rehabilitation on brain neuroplasticity in MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
6
0
1
Order By: Relevance
“…Corticospinal plasticity is exercise-dependent (34,35) and influenced by various factors (36,37), such as aerobic exercise (22,(38)(39)(40), resistance training (22,40), as well as interlimb coordination (41,42). Previous studies that assessed corticospinal plasticity using TMS in healthy participants and in chronic stroke survivors, reported that interlimb coordination and especially inphase bilateral movement has the strongest effect on corticospinal plasticity (43)(44)(45)(46).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 1 more Smart Citation
“…Corticospinal plasticity is exercise-dependent (34,35) and influenced by various factors (36,37), such as aerobic exercise (22,(38)(39)(40), resistance training (22,40), as well as interlimb coordination (41,42). Previous studies that assessed corticospinal plasticity using TMS in healthy participants and in chronic stroke survivors, reported that interlimb coordination and especially inphase bilateral movement has the strongest effect on corticospinal plasticity (43)(44)(45)(46).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Motor symptoms in RRMS are associated with changes in corticospinal tract integrity and neuroplasticity (19)(20)(21)(22)(23)(24)(25). The corticospinal tract is one of the major motor descending pathways 4 providing voluntary motor function in humans (26).…”
Section: Introductionmentioning
confidence: 99%
“…Corticospinal plasticity is exercise-dependent [ 32 , 33 ] and influenced by various factors [ 34 , 35 ], such as aerobic exercise [ 20 , 36 38 ], resistance training [ 20 , 38 ], as well as interlimb coordination [ 39 , 40 ]. Previous studies that assessed corticospinal plasticity using TMS in healthy participants and in chronic stroke survivors, reported that interlimb coordination and especially in-phase bilateral movement has the strongest effect on corticospinal plasticity [ 41 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conducting such studies, a way forward may also include further development of relevant (fast-responding) functional brain outcomes that are sensitive to exercise. 6…”
mentioning
confidence: 99%
“…In addition to conducting such studies, a way forward may also include further development of relevant (fast-responding) functional brain outcomes that are sensitive to exercise. 6 The many beneficial effects of exercise in MS implicate that it is already strongly recommended to people with MS. 7 Nevertheless, it is of utmost importance to both patients and health professionals to determine if exercise has disease-modifying effects, as this would offer a new supplementary treatment option almost free of side effects. As for the future, some cautious optimism does exist as a recent international initiative-Moving exercise research in MS forward (the MoXFo initiative)-has gathered more than 50 researchers aiming to accelerate discoveries in this field.…”
mentioning
confidence: 99%